Analisa Gambaran Perilaku Lansia Dalam Menjaga Kesehatan Di Kelurahan Dusun Besar Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2021 - Handayani, Tita Septi; Samidah , Ida; Murwati , Murwati (Jurnal Pakar Kesehatan, 2025)
The elderly are a vulnerable group prone to physical, mental, and social decline, thus requiring special attention in maintaining their health. This study aims to analyse the health-related behaviours of the elderly in Dusun Besar Village, the service area of Jembatan Kecil Health Centre in Bengkulu City, in 2021. The research method employed a descriptive approach with 60 elderly respondents selected using purposive sampling. Data were collected using a questionnaire and analysed descriptively.